Measuring the Effect of Chemicals on the Growth and Reproduction of Caenorhabditis elegans - Lee, So Young; Kang, Kyungsu (JOURNAL OF VISUALIZED EXPERIMENTS, 2017)
Toxicological evaluation is crucial for understanding the effects of chemicals on living organisms in basic and applied biological science fields. A non-mammalian soil round worm, Caenorhabditis elegans, is a valuable model organism for toxicology studies due to its convenience and lack of animal ethics issues compared with mammalian animal systems. In this protocol, a detailed procedure of toxicological evaluation of chemicals in C. elegans is described. A clinical anticancer drug, etoposide, which targets human topoisomerase II and inhibits DNA replication of human cancer cells, was selected as a model testing chemical. Age-synchronized C. elegans eggs were exposed to either dimethyl sulfoxide (DMSO) or etoposide, and then the growth of C. elegans was monitored every day for 4 days by the stereo microscope observation. The total number of eggs laid from C. elegans treated with DMSO or etoposide was also counted by using the stereo microscope. Etoposide treatment significantly affected the growth and reproduction of C. elegans. By comparison of the total number of eggs laid from worms with different treatment periods of chemicals, it can be decided that the reproductive toxicity of chemicals on C. elegans reproduction is reversible or irreversible. These protocols may be helpful for both the development of various drugs and risk assessment of environmental toxicants.